THE EFFECT OF THINK PAIR SHARE (TPS) LEARNING MODEL ASSISTED BY MEDIA INTSTRUCSIONAL VIDEO AND INTERPERSONAL INTELLIGENCE ON STUDENT LEARNING OUTCOMES IN SOCIAL STUDIES SUBJECTS IN CLASS VII OF SMP NEGERI 4 PERCUT SEI TUAN - Rizky Mawarni Pulungan; Daulat Saragi; Samsidar Tanjung (SENSEI RESEARCH CENTER, 2021)
The objectives of this study were to determine the differences in social studies learning outcomes taught by the TPS model and the TPS model assisted by video media for students to determine the difference in social studies learning outcomes of students who have high interpersonal intelligence with students who have low interpersonal intelligence in students. And then this is to determine the interaction between learning models and interpersonal intelligence in influencing student learning outcomes in social studies subjects for students. The population in this study were all class VII students of SMP Negeri 4 Percut Sei Tuan T.A 2020/2021, totaling 126 students divided into four classes, namely, class VIIa, VIIb, VIIc and VIId. The experimental class was given learning treatment with the Think-Pair-Share (TPS) learning model and the control class was given the Think-Pair-Share (TPS) learning model assisted by video learning media. The instruments used consisted of: social studies learning outcomes test. Data analysis was performed using two-way ANOVA. From the description above it can be concluded that: There is a significant difference in social studies learning outcomes that are taught using the TPS model and the TPS model assisted by video media for the seventh grade students of SMP Negeri 4 Percut Sei Tuan. There is a significant difference in social studies learning outcomes of students who have high interpersonal intelligence and students with low interpersonal intelligence in students who are taught using the TPS model assisted by video media. There is an interaction between the learning model and interpersonal intelligence in influencing student learning outcomes in social studies subjects in class VII students of SMP Negeri 4 Percut Sei Tuan.